ANALISIS STUDI KELAYAKAN BISNIS “NASI KEBULI NAZAR” DITINJAU ASPEK PEMASARAN DAN KEUANGAN - Hanif Nur Rohmawati; Moh Afrizal Miradji; Ach Irwansyah; Sherly Amalia Rahmadanti; Sendy Jadi Mahanani; Chindiani Putri Ningsih; Erika Virza Ananda; Nisa Ardi Ningrum; Hanif N. Rohmawati (.Universitas PGRI Adi Buana, 2023)
This research was conducted to identify the feasibility of the Nasi Kebuli Nazar business which was examined by analyzing marketing aspects and analyzing financial aspects. On the financial aspect with Payback Period (PP) analysis, Net Present Value (NPV), Profitability Index (PI). The results of the study found that the Kebuli Nazar Rice Business from a marketing aspect can be declared feasible because of quality products, affordable prices and commensurate with the products offered, and also the variety of products that can be reached by the community. And the results of the analysis of financial aspects, this business is feasible with a business life of 5 years with a discount rate of 10%. Analysis of the financial aspects shows the PP results for 4 months 5 weeks, the NPV value is Rp. 79,961,469, and a PI of 2.17%.